IMMIGRATION AND LARGE BANKNOTES. (12th November 2012) - Fischer, Andreas M.
Abstract : Do immigrants have a higher demand for large-denominated banknotes than natives? This micro study examines whether banknote orders for CHF 1, 000 notes are concentrated in Swiss municipalities with a high foreign-to-native ratio. The evidence for 251 Swiss municipalities finds that immigrants hoard fewer CHF 1, 000 banknotes than natives. This empirical result means that immigration reduces seigniorage (per person) as measured by banknote orders. A 1% increase in the immigrant-to-native ratio is coincident with a reduction in banknote orders by CHF 4, 000. This reduction is attributed to specific traits linked to immigrants.